Light Metals 2016 - Williams, Edward (The Minerals, Metals & Materials Series, 2016)
The Light Metals symposia are a key part of the TMS Annual Meeting & Exhibition, presenting the most recent developments, discoveries, and practices in primary aluminum science and technology. Publishing the proceedings from these important symposia, the Light Metals volume has become the definitive reference in the field of aluminum production and related light metal technologies. The 2016 collection includes papers from the following symposia: 1.Alumina and Bauxite 2.Aluminum Alloys, Processing, and Characterization 3.Aluminum Reduction Technology 4.Cast Shop Technology 5.Electrode Technology 6.Strip Casting.